Second Five Year Plan Development Programme (1956-1957) Government of Bombay - Planning Commission (Planning Commission, 1956)
The Draft Second Five-Year Plan of Bombay State which was published in November 1955 has now been finalised in consultation with the Planning Commission and after taking into account the comments of the State Legislature and the public. the State Plan, as finalised, involves a total outlay of Rs. 266 25 crores including the Central assistance in terms of loans and grants which is expected to be received for several schemes included in the Plan. In respect of the following schemes which are regarded as Central schemes only the share of expenditure which the State Government will have to bear during the Second Plan period has been shown in the State Plan. The Central share of expenditure likely to be incurred in Bombay State as shown below is therefore, in addition to the outlay by the State Government.
Government of Bombay